2016
DOI: 10.4018/ijicthd.2016010101
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Learning

Abstract: Hybrid learning has been utilized as a transitional learning method to make advantage of both face-to-face and online learning platforms. In this article, the authors explored how faculty members perceive using simultaneously multiple platforms in higher education such as face-to-face, online, and hybrid platforms in teaching. In this study, the authors examined how faculty members defined hybrid learning. They also explored how the participants perceive both hybrid and online learning as vehicles for higher e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
(5 reference statements)
0
4
0
1
Order By: Relevance
“…Oleh karena itu, untuk mendukung kualitas proses dan prestasi belajar siswa di masa pandemi covid-19 yang sesuai untuk pembelajaran teori maupun praktik mata pelajaran produktif siswa SMK banyak menggunakan Blended Learning dengan model pembelajaran yang sesuai. Pembelajaran kombinasi (blended learning) adalah sebuah metode pendidikan jarak jauh menjadi fokus utama yang didukung dengan pendidikan tradisional (tatap muka) (Abdelrahman & Irby, 2016). blended learning adalah model pembelajaran yang mengintegrasikan inovasi dan kemajuan teknologi melalui sistem online learning dengan interaksi dan partisipasi dari model pembelajaran tradisional (Hendrayati & Pamungkas, 2003).…”
Section: Pendahuluanunclassified
“…Oleh karena itu, untuk mendukung kualitas proses dan prestasi belajar siswa di masa pandemi covid-19 yang sesuai untuk pembelajaran teori maupun praktik mata pelajaran produktif siswa SMK banyak menggunakan Blended Learning dengan model pembelajaran yang sesuai. Pembelajaran kombinasi (blended learning) adalah sebuah metode pendidikan jarak jauh menjadi fokus utama yang didukung dengan pendidikan tradisional (tatap muka) (Abdelrahman & Irby, 2016). blended learning adalah model pembelajaran yang mengintegrasikan inovasi dan kemajuan teknologi melalui sistem online learning dengan interaksi dan partisipasi dari model pembelajaran tradisional (Hendrayati & Pamungkas, 2003).…”
Section: Pendahuluanunclassified
“…Similar purpose to analyze the outcome of HL implementation, a study conducted by Widdy (2021) showed the HL strategy had a significant effect on ameliorating learning outcomes in implementing the concept and comprehensive attitude in students. The closest study, which focuses on how faculty members perceived the HL implementation, was conducted by Abdelrahman and Irby (2016). The result shows that there are various definitions of HL from the students instead of gaining a single definition of HL.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, when the pandemic strikes the educational system at the implementation level, schools are not built to implement HL. Abdelrahman and Irby (2016) have claimed that HL provides accessibility; meanwhile, classical Physics class offers quality. The study focuses on the resulting test as an instrument to measure the impact.…”
Section: Introductionmentioning
confidence: 99%
“…In simple terms, teachers should learn about hybrid learning by managing hybrid learning by utilizing every possible online and digital resource. Hybrid learning is a pedagogical approach that combines face-to-face (F2F) instruction with computermediated instruction (Abdelrahman & Irby, 2016). The terms hybrid learning, blended learning, and mixed-mode learning can be used interchangeably in recent research.…”
Section: Introductionmentioning
confidence: 99%
“…This combination is pedagogically significant, facilitating students to direct learning by selecting available learning strategies and materials that best suit their qualities and needs. In addition, it has a direction toward accomplishing educational plan learning objectives (Abdelrahman & Irby, 2016).…”
Section: Introductionmentioning
confidence: 99%